Marginalisasi dan Subordinasi terhadap Perempuan dalam Film Kim Ji Young: Born 1982 dan Film Kartini: Suatu Kajian Sastra Bandingan - Roza Muchtar; Yenni Hayati (Universitas Pendidikan Indonesia, 2022)
The purpose of this study is to describe 1) marginalization and subordination in Kim Ji Young: Born 1982’s film, 2) marginalization and subordination in Kartini’s film, and 3) similarities and differences in Kim Ji Young: Born 1982’s film and Kartini’s film. This research uses a descriptive-qualitative method with a comparative literature review. The approach used in this research is a feminist approach. The data of this research are the speeches of characters and scenes without dialogue in Kim Ji Young: Born 1982’s film and the Kartini’s film which contain forms of marginalization and subordination of women. The data source or object of study in this study is the Kim Ji Young: Born 1982’s film which was produced in 2019 and the Kartini’s film which was produced in 2017. The data collection technique used in this study was the note-taking technique. The process of analyzing the data in this study consisted of three stages. First, classifying the data. Second, interpreting data. Third, conclude the results of data analysis. The results of this study indicate that there are similarities and differences in the forms of marginalization and subordination of women. The similarity in the form of marginalization is in the form of restrictions on women's movement space. The similarity in the form of subordination in the form of the position of women is considered unimportant so that they are subordinated to men.